An economic analysis of the 2010 proposed settlement between the department of justice and credit card networks - Scott Schuh; Oz Shy; Joanna Stavins; Robert Triest (Federal Reserve Bank of Boston, 2011)
In 2010, the Department of Justice (DOJ) filed a lawsuit against the credit card networks American Express, MasterCard, and Visa for alleged antitrust violations. We evaluate the extent to which the recently proposed settlement between the DOJ and Visa and MasterCard (henceforth, Proposed Settlement) is likely to achieve its central objective: ...to allow Merchants to attempt to influence the General Purpose [Credit] Card or Form of Payment Customers select by providing choices and information in a competitive market. In word and spirit, the Proposed Settlement represents a significant step toward promoting competition in the credit card market. However, we find that merchants are unlikely to be able to take full advantage of the Proposed Settlement's new freedoms because they currently lack comprehensible and complete information on the full and exact merchant discount fees for their customers' credit cards. We analyze the likely consequences of this information problem, and consider ways in which it could be remedied. We also evaluate the probable welfare consequences of allowing merchants to impose surcharges to reflect the fees associated with the use of payment cards.
Keywords: E42; G29; D14; 330; Kreditkartenorganisation; Kartellrecht; Kartellrecht; Schiedsgerichtsbarkeit; Kreditkarte; Markt; Wettbewerb; USA